Programa de estrategias metodológicas de acompañamiento pedagógico y desempeño profesional de los docentes de educación primaria de la I.E. N° 81015- Trujillo - Cotrina Yraita, Silvia Marleni (2019)
The objective of this research was to demonstrate that the application of the methodological strategy program of pedagogical accompaniment proposed improves the professional performance of primary school teachers in the province of Trujillo. The research was conducted with a sample of sixty teachers belonging to educational institutions No. 81015 "Carlos E. Uceda Meza" - Trujillo (experimental group) and No. 80824 "José Carlos Mariátegui" - El Porvenir (control group) using a design quasi-experimental in intact groups with pre and posttest. In both groups, the professional performance of teachers in the domains was observed directly: preparation for student learning, teaching for student learning and participation in the management of the school articulated with the community, contained in the Framework of Good Teaching Performance (RM N ° 0547 - 2012 - ED); observations that were recorded in an observation guide adapted from the evaluation sheet of the teaching performance of the Peruvian Ministry of Education, by the author of the investigation. The hypothesis was formulated in which the application of the methodological program of teaching support proposed, improves the professional performance of the teacher, comparing the levels of development of the average professional performance of the teachers of the experimental and control groups after the application of the program, using the Student's t-test, with α = 0.05. The results of the test yielded a value of p = 0.00, making it possible to reject the null hypothesis and conclude that the application of the program in reference significantly improves the professional performance of the teachers in an integral manner. Likewise, the level of development of the professional performance of all the teachers of the experimental group in each of the domains considered after applying the proposed program, was qualified as "achieved", that is, they fully and satisfactorily fulfilled what is required in the guide. of observation used.